2019
DOI: 10.1139/cjc-2018-0138
|View full text |Cite
|
Sign up to set email alerts
|

A novel fluorescent sensor based on 4-(diethylamino)-2-(hydroxy)-phenyl imine functionalized naphthalimide for highly selective and sensitive detection of CN and Fe3+

Abstract: In this work, a novel sensor molecule HB1, based on a 4-(diethylamino)-2-(hydroxy)-phenyl imine functionalized naphthalimide derivative, was successfully designed and synthesized. Interestingly, the HB1 showed fluorescence identification ability for CN– in DMSO/H2O (8:2, v/v) solution. After addition of CN– into the HB1 solution, the fluorescence intensity of HB1 solution could be enhanced obviously. The anti-disturbance experiments demonstrated that other anions could not interfere in the detection of CN–. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It is further pointed out that naphthalimide with amine substituent at the 4-position is well established as a fluorescent probe for its involvement in the internal charge transfer phenomenon. 25 Before examining the interaction in fluorescence, the quantum yield 26 of 1 ( Φ F = 0.31) was determined in DMF. Emission changes on excitation at 460 nm were only noted with CN − , F − , AcO − , and H 2 PO 4 − .…”
Section: Resultsmentioning
confidence: 99%
“…It is further pointed out that naphthalimide with amine substituent at the 4-position is well established as a fluorescent probe for its involvement in the internal charge transfer phenomenon. 25 Before examining the interaction in fluorescence, the quantum yield 26 of 1 ( Φ F = 0.31) was determined in DMF. Emission changes on excitation at 460 nm were only noted with CN − , F − , AcO − , and H 2 PO 4 − .…”
Section: Resultsmentioning
confidence: 99%
“…What's more is that the lowest detection limits of supramolecular OGMs for I − , N 3 − , CN − , L-Trp and L-His are much lower than those of the reported chemosensors for these anions and l -amino acids (Table 1 and Table S2, ESI†), which indicated that these five OGMs are capable of detecting target anions and l -amino acids sensitively. 47–66…”
Section: Resultsmentioning
confidence: 99%
“…What's more is that the lowest detection limits of supramolecular OGMs for I À , N 3 À , CN À , L-Trp and L-His are much lower than those of the reported chemosensors for these anions and L-amino acids (Table 1 and Table S2, ESI †), which indicated that these five OGMs are capable of detecting target anions and L-amino acids sensitively. [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] To further exploit the practical application of these OGMs (including OGFe, OGCa, OGCu, OGCo and OGNi), the fluorescent display films based on OGMs were prepared by pouring a heated cyclohexanol solution of the OGMs on a clean glass surface and drying in air. These metallogel films show bright blue fluorescence emission under 365 nm UV light (Fig.…”
mentioning
confidence: 99%
“…-NO 2 [20][21][22][23], and CN − [24][25][26][27][28][29]. Although these sensors show great potential for ion sensing, their practical application is limited by drawbacks such as intrinsic toxicity, optical instability, water insolubility, and susceptibility to interference, especially those developed for the detection of CN − .…”
Section: Introductionmentioning
confidence: 99%